The identificaction of unaccompanied foreign minors and the voluntary guardian in Italy: an example to be followed by the EU? - Tassinari, Francesca (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The Italian Law n. 47 of 2017 on dispositions upon protection measures of foreign unaccompanied minors, represents the first normative text, which contemplates, in a uniform way, the protection of unaccompanied minors in the EU. On one side, it establishes a multidisciplinary proceeding for the identification of the minor and for the determination of his/her minor age (art. 5). On the other, it stand out the legal figure of a «volunteer guardian», institution that protect unaccompanied minors who arrive at the Italian territory (art. 11). However, the lack of coordination among Member States threats the practice efficacy of those legal provisions, which coercive force is confined through the Italian territory. We discuss upon the need of harmonizing the different states’ practices through a legislative intervention of the EU.
Keywords: Unaccompanied foreign minors; identification; volunteer guardian; harmonisation; Italy; European Union